Developing Children's Literacy Understanding Through the Analysis of Indonesian Folklore: A Qualitative Study in Elementary Schools - Ria Kasanova (Aksara Shofa, 2025)
This study investigated the utilisation of Nusantara folktales in improving children's reading skills in primary schools using qualitative methodology. Data were collected through interviews, observations and document analyses, involving teachers and students in lower grades from various primary schools. The results showed that Nusantara folktales have a substantial impact on the development of children's reading skills, increasing students' engagement, encouragement and comprehension of written material. Folktales assist in the development of critical thinking skills and the assimilation of moral and cultural principles. Nusantara folktales have the potential to be a valuable educational tool for improving children's literacy skills in primary schools. This study offers valuable insights for educators in developing literacy learning programmes that incorporate folktales and provides a basis for further research into the long-term effects and contextual elements that shape their implementation.